Iatrogenic Creutzfeldt-Jakob Disease, Final Assessment - Paul Brown; Jean-Philippe Brandel; Takeshi Sato; Yosikazu Nakamura; Jan MacKenzie; Robert G. Will; Anna Ladogana; Maurizio Pocchiari; Ellen W. Leschek; Lawrence B. Schonberger (Emerging Infectious Diseases, 2012)
The era of iatrogenic Creutzfeldt-Jakob disease (CJD) has nearly closed; only occasional cases with exceptionally long incubation periods are still appearing. The principal sources of these outbreaks are contaminated growth hormone (226 cases) and dura mater grafts (228 cases) derived from human cadavers with undiagnosed CJD infections; a small number of additional cases are caused by neurosurgical instrument contamination, corneal grafts, gonadotrophic hormone, and secondary infection with variant CJD transmitted by transfusion of blood products. No new sources of disease have been identified, and current practices, which combine improved recognition of potentially infected persons with new disinfection methods for fragile surgical instruments and biological products, should continue to minimize the risk for iatrogenic disease until a blood screening test for the detection of preclinical infection is validated for human use.